SPATIAL ESTIMATION OF GROUNDWATER QUALITY, HYDROGEOCHEMICAL INVESTIGATION, AND HEALTH IMPACTS OF SHALLOW GROUNDWATER IN KABUL CITY, AFGHANISTAN - Hamidi, Mohammad Daud; Kissane, Stephen; Bogush, Anna A.; Karim, Abdul Qayeum; Sagintayev, Janay; Towers, Sam; Greenwell, Hugh Christopher (Sustainable Water Resources Management, 2022)
The management of groundwater in densely populated areas with no centralized water treatment is critical for the prevention of diseases and maintaining sanitation. Here, we determine the bacteriological and chemical characteristics of groundwater in Kabul city, a resource that 4.1 million individuals rely on. Groundwater samples were analyzed from 41 newly established piezometric wells across Kabul, and data were compared with the last detailed study, undertaken in 2007, to understand contamination trends in an area that has undergone significant development and social changes. Piper diagrams, Gibbs diagrams, correlation analysis, and bivariate plots examine the hydrogeochemical and natural occurring processes of groundwater. The average concentration of cations followed the order Na+  > Mg2+  > Ca2+  > K+, and anions HCO3− > NO3− > Cl− > SO42− > F with Gibbs diagrams indicating mainly rock-weathering influence groundwater chemistry. An increase in nitrate (NO3−) and E. coli indicates anthropogenic activities impacting the shallow groundwater quality, with significantly elevated nitrate (over 50 mg/L) and E. coli (up to 250 CFU/100 mL). The increasing presence of E. coli and NO3− in the shallow groundwater of Kabul city in turn suggests problematic links to the prevalence of waterborne diseases. Additionally, the water quality index (WQI) was used to assess groundwater quality, and rank its suitability for drinking purposes. The WQI analysis showed that less than 35% of shallow groundwater samples had good water quality. The findings of this study are crucial for the development and sustainable management of groundwater in the city. In short term, we propose interventions such as point-of-use (POU) water purification which may offer temporary respite for waterborne disease prevention. Kabul city requires immediate attention to developing sustainable groundwater management policies, expansion of the water supply network, groundwater quality monitoring, and wastewater management.
Keywords: Type of access: Open Access; Water quality; Water quality index; WQI; Sustainable groundwater management; Kabul city